TINJAUAN YURIDIS ATAS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 21/PUU-XIV/2016 TENTANG PEMUFAKATAN JAHAT ATAS KASUS PERPANJANGAN KONTRAK PT.FREEPORT - MUHAMMAD ROBBY ARWANDI (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstrackThis thesis aims to find out how the judges of the Constitutional Court in deciding cases of judicial review and the implications of the offense on the case of the conspiracy of Article 15 of the Corruption Act, by the applicant Setya Novanto. In the verdict of judicial review of the law on Uud 1945 mahmakah constitution holds on 3 principles namely, legal, sociological, philosophical asa. In this test the judge accepts the petition and grants it.Method This research is a type of research library (library research) or ordinary law research methods commonly called doctrinal legal research This research is analytical descriptive that is arranging systematically describing the judges' legal considerations and the implication of decision Number 21 / PPU-XIV / 2016 and then analyzing it juridically. The result of this research reveals that in deciding this case the judge is less precise in declaring the case in terms of consideration, and the implications of this decision should be more clearly made not to all the legal consequences to be lost because of the outcome of this decisionKeywords : Decision of the Constitutional Court Number 21 / PUU-XIV / 2016 Concerning the Evil Conspiracy